An Approach to Assessing the Linguistic Difficulty of Tasks. (18th December 2019) - Pallotti, Gabriele
This article proposes an approach to assessing the linguistic difficulty of tasks, that is, the linguistic features involved in performing a communicative task that may make it more or less challenging for language learners. The procedure follows the methodology proposed by Pallotti (2019 ) for operationalizing task interactional difficulty. This consists, firstly, in identifying what linguistic-communicative features are particularly difficult for language learners, based on previous research showing that they appear late in the course of acquisition. Secondly, native speakers' performance is observed in order to determine which tasks most involve these difficult linguistic features. The dimensions observed in this study concern lexical diversity and sophistication, morphological complexity, and length and depth of syntactic constructions. Data come from 10 native speakers of Italian performing 5 communicative tasks. Results show that different dimensions of linguistic difficulty are relatively independent of each other, and that inter-individual variation is rather limited as regards the lexicon and morphology, but more pronounced for syntax. Implications for SLA research, Task-Based Language Teaching and Task-Based Language Assessment are discussed.